Evaluation of IFN-γ enzyme-linked immunospot assay (ELISPOT) as a first-line test in the diagnosis of non-immediate hypersensitivity to amoxicillin and penicillin - Sedláčková, Lenka; Průcha, Miroslav; Poláková, Ingrid; Míková, Blanka (Prague Medical Report, 2018)
The current diagnostic algorithm for beta-lactam allergy is based on skin and provocation tests, both of which carry a certain risk of inducing hypersensitivity reactions. Thus, non-invasive in vitro tests reliable enough to replace skin and provocation tests at least in a portion of patients are desirable. We aimed to verify the utility of IFN-γ ELISPOT as a first-line test in patients with suspected non-immediate hypersensitivity reaction to amoxicillin (AMX) and penicillin (PNC). The prospective observational study included 24 patients with recent, suspected non-immediate hypersensitivity reaction to AMX or PNC and 6 recently-exposed healthy subjects. In vitro tests were performed in all patients and healthy subjects: a) IFN-γ ELISPOT with PNC, AMX and amoxicillin plus clavulanic acid (AMX-CL); b) penicillin specific IgE; c) basophil activation test (BAT). Skin and provocation tests followed only in certain patients. IFN-γ ELISPOT results with PNC and AMX stimulation did not differ from the unstimulated condition. The highest IFN-γ responses to AMX-CL were close to previously published criteria in three patients; one of which had true hypersensitivity according to drug provocation tests. Five patients with confirmed hypersensitivity by skin tests showed no response to the culprit antibiotic on IFN-γ ELISPOT assay. Our results did not support the utility of IFN-γ ELISPOT in the diagnosis of mild, non-immediate hypersensitivity to amoxicillin and penicillin.
Keywords: mužské pohlaví; Male; Humans; Female; lidé; Penicillins; Prospective Studies; Anti-Bacterial Agents; Middle Aged; ženské pohlaví; lidé středního věku; léková alergie; imunoenzymatické techniky; Amoxicillin; Drug Hypersensitivity; ELISPOT; prospektivní studie; antibakteriální látky; dospělí; Adult; peniciliny; Enzyme-Linked Immunospot Assay; amoxicilin; Immunoenzyme Techniques